2018
DOI: 10.1111/hsc.12614
|View full text |Cite
|
Sign up to set email alerts
|

An explorative evaluation study of the mechanisms underlying a community-based fitness centre in Denmark - Why do residents participate and keep up the healthy activities?

Abstract: Health-risk behaviour like physical inactivity is more evident in deprived neighbourhoods than in nondeprived neighbourhoods, and in the former knowledge is lacking as to what causes effects in interventions on physical activity. A possible contribution to physical activity interventions is community engagement, which has been shown to be effective for changing health-risk behaviour, but more knowledge is needed on "the active ingredients" or mechanisms that make interventions work. The aim of this study was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
(40 reference statements)
0
2
0
1
Order By: Relevance
“…Room for socialising was much in demand in non-profit fitness clubs in contrast with commercial centres where places to meet before and after almost are non-existent. Good social relations and a sense of community were highlighted in several studies [ 42 44 ], but for the current participants, it differed because they prioritised social relations beyond training. Studies of regular fitness centre users in commercial centres also stressed friendship both inside and outside the fitness centre [ 45 ].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Room for socialising was much in demand in non-profit fitness clubs in contrast with commercial centres where places to meet before and after almost are non-existent. Good social relations and a sense of community were highlighted in several studies [ 42 44 ], but for the current participants, it differed because they prioritised social relations beyond training. Studies of regular fitness centre users in commercial centres also stressed friendship both inside and outside the fitness centre [ 45 ].…”
Section: Discussionmentioning
confidence: 93%
“…Generally, studies concluded motivation related to improving body appearance and performance, reducing health issues or improving mental well-being [ 39 , 46 50 ]. In only three studies the atmosphere was associated with feelings of being comfortable, valued and welcomed [ 34 , 42 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 76 papers [ 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 ,…”
Section: Resultsunclassified